Obtaining informed consent in veterinary clinical trials mini review - Frederick, Carol E. (Frontiers in Veterinary Science, 2024)
In September 2023 the US Food and Drug Administration (FDA) released draft guidance for comment about how informed client consent for companion animal clinical trials should be obtained. This guidance has the potential to substantially change how informed consent documents are written and presented to clients in the veterinary community. It provides specifics not only about how to obtain informed consent from owners but also the timeframe within which consent should be obtained, the formatting and language in the consent forms, and details on elements that are required to be in these consent forms. These changes will involve additional efforts by investigators to ensure compliance yet might lead to increased owner compliance and higher enrollment in clinical studies with subsequent benefits for all.